Development of a multilateral business management application for individual microentrepreneurs in the beauty industry (Research, Society and Development, 2022)
Marketing is a key tool in the exchange and sales relationships in the commercial environment. For a better relationship with the target audience, it is necessary to know their needs and bring a better experience in the services and products that are acquired by the final consumer. The purpose of this article is to base and propose an application of aesthetic services that, together with the composition of the 4 strategic P's of marketing, will help individual micro-entrepreneurs in the aesthetics sector to manage scheduling requests, brand coverage and relationship with the public. -target. In this sense, the present work is classified as applied scientific research, being therefore adopted for the construction of the application for the Android and iOS mobile platforms, the Flutter application development framework and the Clean Architecture methodology idealized by Robert C. Martin. The proposal advances in relation to the customer segment served, following a standard concept of mobile application development, since the application architecture was built in order to facilitate optimization and future modifications in case new technical demands arise, in addition to meeting requests for changes based on the behavior and requirements of providers and consumers. Thus, the developer responsible for the application will be able to apply corrections and updates in the shortest possible time according to the demand raised.